Graphitic porous carbon fabricated from waste coffee grounds for supercapacitors - Thao Phuong Nguyen; Toan Ngoc Vu; Duy Huynh Minh Nguyen; Thy Thi Anh Ho; Minh Hong Le; Son Hoang Thai Ton; Han Ngoc Tran; Tam Thi My Luu; Son Truong Nguyen; Van Thi Thanh Ho (Next Materials)
Given the increasing global energy demand and the urgent need for sustainable energy storage materials, especially for supercapacitors. Coffee grounds have been investigated as a potential carbonaceous precursor for fabricating activated carbon. Interestingly, we applied hydrothermal carbonization at a relatively low temperature of 240 ℃, followed by chemical activation using KOH at 650 ℃ with a low KOH:hydrochar ratio (1.5:1) while still achieving high surface area (976.34 m2 g−1), well-developed pore structures, and excellent ion transport properties. Such synergistic conditions contribute to enhanced energy efficiency, economic viability, and environmental sustainability relative to earlier studies. SEM and TEM analysis were conducted to reveal the formation of a hierarchical pore network. XRD confirmed the transformation into an amorphous carbon structure with rich aromatic characteristics while FT-IR spectra indicated the progressive removal of organic functional groups and an enhancement in thermal stability, and Raman Spectroscopy provided more evidence for the presence of graphitic interfaces. Electrochemical measurements (CV, GCD, and EIS) demonstrated that graphitic porous carbon derived from coffee grounds provided a specific capacitance of 150 F g−1 at 0.5 A g−1 with over 92.4 % retention of its initial capacity after 1150 cycles at a current density of 10 A g−1. This study offers an effective coffee-waste disposal method while contributing to the circular economy with sustainable, high-performance carbon materials for supercapacitors.